Cover Feature: Electrophilic Organobismuth Dication Catalyzes Carbonyl Hydrosilylation (Chem. Eur. J. 56/2020). Issue 56 (3rd September 2020) - Kannan, Ramkumar; Balasubramaniam, Selvakumar; Kumar, Sandeep; Chambenahalli, Raju; Jemmis, Eluvathingal D.; Venugopal, Ajay
Abstract : A highly electrophilic organobismuth dication was designed by controlling the energy of the acceptor orbitals. Structure of the dication polarizing three carbonyl moieties has been deduced by X‐ray structure analysis and NMR spectroscopy. Demonstration of catalytic carbonyl hydrosilylation is a proof of concept for designing desired level of electrophilicity at bismuth. More information can be found in the Communication by E. D. Jemmis, A. Venugopal, et al. on page 12717 .